SPAIN AND THE RESPONSIBILITY TO PROTECT: AN ACTIVE COMMITMENT - Vázquez Rodríguez, Beatriz (Journal of the Spanish Institute for Strategic Studies, 2018)
spain showed its commitment to the idea of the responsibility to protectfrom the very start of discussions at the United nations, and hassince proven it in statements on the subject, at both the general assemblyand the security council, in interactive dialogues on thematicresolutions and situations of armed confl ict that have given rise to thenotion being invoked. one of spain’s priorities as a non-permanentmember of the security council for the biennium 2015-2016 is to pushfor the eff ective implementation of the responsibility to protect and forthe introduction of limits on the use of veto in situations of serious andmassive violations of human rights.spain has also participated very actively in specifi c initiatives for thepromotion of the concept as a member of the group of friends of theresponsibility to protect and as a member state of the global networkof responsibility to protect focal points. its commitment to theresponsibility to protect at the domestic level can also be seen in theinclusion of this concept in spain’s external action strategy documents.